2D Finger Motion Tracking, Implementation for Android Based Smartphones - Khosravi Nahouji, Maryam (My University, 2012)
Human computer interaction grows day by day and nowadays it has been entered many aspects of the life. Through this growth it has covered not only the desktop and laptop PCs but also mobile phones and specifically Smartphones. Therefore it worth to consider this topic and try to make a new functionality for these kinds of interactions. The intention is to find a practical way to make a new use of the video camera of the Android based Smartphones and track a single finger using the camera as sensor. To track an object in Android platform it needs some special prerequisite. It means that there should be a way to make the tracking applicable on Smartphones. for this purpose the solution this work has come up with is to use OpenCV library which is an open source library specialized for computer vision applications. This library is applicable on Android platform and therefore can be considered for our intention. Also considering different methods applied for hand tracking purpose in earlier works which has been studied in this work, the intention was to implement a method which was not been used by later studied works. Therefore the method of tracking used in this work is called “Motion Templates”. This method is a method represented by OpenCV library and used in this work. To reduce the complexity of the work the first mile-stone which is implemented in this work is to track the finger on PC and then try to port the method and algorithm to Android platform. The tracking is done successfully on the PC using this method and it can be recommended as a possible way of tracking to be considered on Android platforms as a future work.
Keywords: Människa-datorinteraktion (interaktionsdesign); Informations- och kommunikationsteknik; Human Computer Interaction; Information & Communication Technology